HUBUNGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL TIKTOK DAN PEMAHAMAN MENGENAI BULLYING PADA SISWA KELAS V SD NEGERI DI KELURAHAN CENGKARENG TIMUR - Zettriz Yuliana; Otib Satibi Hidayat; Imaningtyas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the relationship between the intensity of TikTok usage and the understanding of bullying among fifth-grade students at public elementary schools in Cengkareng Timur, West Jakarta. The research employed a quantitative correlational method, using closed-ended Likert-scale questionnaires as the data collection instrument. A total of 91 students were selected through simple random sampling from two schools. Data analysis revealed a significant positive relationship between TikTok usage intensity and bullying comprehension, with a Pearson correlation coefficient of 0.675 and a significance value of 0.000 (< 0.05). The coefficient of determination showed that 45.6% of students’ understanding of bullying was influenced by their intensity of TikTok usage, while the remaining 54.4% was affected by other factors. These findings support Bandura’s social learning theory, suggesting that exposure to social media content contributes to students’ knowledge and attitudes toward bullying.